Trauma THOMPSON: A Dataset and Realistic Generative Framework for AI Copilots in Emergency Care - Zhuo, Yupeng; Zhang, Eddie; Yu, Xiangchen; Pachpande, Aditya; Kirkpatrick, Andrew W.; Mckee, Jessica; Wachs, Juan (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
We introduce Trauma THOMPSON, a dataset and suite of benchmarks designed to accelerate the development of AI-powered copilots for real-time decision-making in emergency and resource-limited medical settings. This work proposes a method to address a critical bottleneck for future deployment: models trained on simulations may not perform well in the real world. The dataset features 3,717 unscripted, first-person video clips of five emergency procedures, uniquely including "just-in-time" (JIT) interventions that mirror the improvisational nature of field medicine. To obtain realistic patient data without ethical issues and identity concerns that medical data often encounter, we also propose TraumaGen, a novel framework for generating photorealistic patient and wound images from manikins while preserving clinical context. We establish benchmarks for action recognition, anticipation, and visual question answering (VQA), evaluating state-of-the-art models to demonstrate the challenges and potential of our dataset. By focusing on realism and improvisation, Trauma THOMPSON provides a crucial resource and a clear path toward developing and validating robust AI assistants for future deployment in real-world emergency care.